Scalable bacterial cellulose biofilms with improved ion transport for high osmotic power generation. (October 2021) - Wu, Zhuotong; Zhang, Tao; Wang, Baoxiu; Ji, Peng; Sheng, Nan; Zhang, Minghao; Liang, Qianqian; Chen, Shiyan; Wang, Huaping
Abstract: The manufacture of large-sized material with tunable nanochannel size and high ion selectivity is always a challenge for osmotic power generation. Herein, we develop negatively charged carboxymethyl bacterial cellulose membranes (BC-CMC) and positively charged chitosan quaternary ammonium bacterial cellulose membranes (BC-HACC) with adjustable charge density and nanochannel size by in situ culture. The scalable membranes are suitable for rapidly ion selective transmission process. When applying the charged BC membranes for an osmotic energy harvesting device, an output power density of 2.25 W m −2 can be reached. Further connecting 15 units of the charged BC device, the output voltage can reach up to 2.53 V, which can directly power the electronic devices. This work highlights the advantage of large-scale preparation by the biosynthesis method, which can simultaneously tune the surface properties and nanochannel size of BC to regulate the ion transport behavior. We offer an easy and scalable method to obtain low-cost membranes for high osmotic energy conversion device, providing the feasibility for their large-scale application. Graphical Abstract: ga1 Highlights: This paper offers a simple in situ biosynthetic modification to obtain charged BC membranes. The scalable membranes are suitable for ion selective transmission process. The BC-RED device can achieve an output power density of 2.25 W m −2 . Our work develops low-cost, large-scale charged BC membranes potential in practical osmotic energy collection.